(untitled) (ЕтноАнтропоЗум/EthnoAnthropoZoom, 2019)
It is known that the former socialist societies tend to make major changes in appearance and to forget the socialist past, while turning to a distant past. Skopje is the leader when it comes to promoting the distant past. Thus, the newly built “Ethno Village” or “Macedonian ethno - village” in Skopje is among the many monuments that were built in the last decade. The idea behind the building of a dozen houses that represent copies of former habitats located in several Macedonian regions was to promote the Macedonian tradition and architecture among the Macedonian citizens, but also among the foreigners visiting Skopje. The complex is a result of the predator economic liberalism whose goal is not a good quality culture, but rather to profit from culture. The transformation of culture into merchandize means managed culture or culture not as a way of life, but as a way of consumption, i.e. a market commodity.